HUBUNGAN KONDISI FISIK RUMAH DENGAN KEJADIAN PNEUMONIA PADA BALITA DI DAERAH PERKOTAAN (Studi di Wilayah Kerja Puskesmas Bergas) - Koni Agustyana Wijayanti; Praba Ginandjar; Lintang Dian Saraswati; Retno Hestiningsih (Jurnal Kesehatan Masyarakat (Undip), 2019)
Pneumonia is a disease caused by inflammation, infection and results in critical infection in respiratory tract. Pneumonia becomes the major cause of toddlers’ death in Indonesia. The cause of pneumonia can be caused by environmental factors in the home that includes a physical home environment. The aim of this research is analyse association between physical housing condition with a disease incidence of Pneumonia toddlers in urban area. This research is an analytical observational research using cross-sectional approach. The population of this research is the toddlers in Bergas local government clinic work area which has 100 respondents. The bivariate analysis is using Chi Square. The result were analyzed by chi square analysis of floor type (p = 0,715), wall type (p = 0,675), temperature (p = 0,016), humidity (p = 0,228), ventilation area (p = 0,728). There is an association between temperature (p value 0,016) with incidence of pneumonia toddlers’. There is no association between floor type, wall type, humidity, ventilation area with incidence of pneumonia toddlers.  The local government clinic of Bergas are expected to hold a socialization concerning to pneumonia and earthy-healthy house towards mothers with toddlers.